Efficacy of localized intradermal microinjection of tranexamic acid at a concentration of 4 mg/ml in the treatment of melasma in Syria - Al-Manssour, Heba Ghassan; Roumieh, Abdulhalim (Journal of medical and pharmaceutical sciences, 2022)
Background: Melasma is a common acquired hyperpigmented dermatosis due to a disorder in the function of the melanogenesis process. Nowadays, there are many used treatments for melasma but it is still a big cosmetic problem. The Aim of our study is to evaluate the efficacy and safety of intradermal microinjection of tranexamic acid TXA in the treatment of melasma in Syrian women. Methods: A total of 34 women with melasma, attending Tishreen University Hospital in Lattakia-Syria from January 2020 to January 2021 were included in this prospective (before and after) study. We applied topical anesthesia then we injected 0.05 ml TXA (4 mg/ml) intradermally into the melasma lesions at 1 cm intervals by using a 30-gauge insulin syringe. We repeated this procedure every 2 weeks for 12 weeks. A clinical investigator evaluated the results by using the modified Melasma Area and Severity Index (mMASI) at baseline and at 4, 8, and 12 weeks. Patients were followed up after 3 months from completing the treatment. Results: The mean mMASI scores decreased from 6.99±3.4 at baseline to 5.98±3.2, 4.59±2.5 and 3.49±2.3 at weeks 4, 8, 12 respectively. This decrease was clinically and statistically significant with a p-value = 0.0001. Our patients did not show serious side effects. Conclusion: According to that, we suggest that localized intradermal microinjection of tranexamic acid at a concentration of 4 mg/ml is an effective and safe therapeutic method for melasma.